Adaptive subtitle and caption coloring using fuzzy analysis - Davoudi, Mohsen; Davoudi, Mehdi; Seifnaraghi, Nima (My University, 2009)
In this paper, a novel approach is proposed for automatic adaptive subtitle color changing based on fuzzy logic. Fuzzy analyzer, the core of this system, changes the color of the subtitle/caption to a 'pleasant' color according to color harmony and the visual perception of the image background colors. Using RGB histograms of background image, the fuzzy analyzer computes the R, G and B values for the color of the subtitle or caption based on fuzzy rules which are designed to satisfy complementary color and subtitle-background color harmony conditions. © 2008 IEEE.
2009 WRI World Congress on Computer Science and Information Engineering, CSIE 2009 --
Keywords: B value; Background image; Color changing; Color harmony; Complementary colors; Fuzzy analysis; Visual perception; Computer science; Fuzzy logic; Fuzzy sets; Color